ATP-responsive laccase@ZIF-90 as a signal amplification platform to achieve indirect highly sensitive online detection of ATP in rat brain. Issue 47 (12th May 2020) - Zhang, Wang; Wang, Chao; Peng, Meihong; Ren, Guoyuan; Li, Kai; Lin, Yuqing
Abstract : ATP-responsive laccase@ZIF-90 acts as a signal amplification platform for indirect and highly sensitive online detection of ATP in rat brain. Abstract : A novel electrochemical online system for indirect, highly sensitive and selective online monitoring of ATP in the cerebral microdialysate is presented based on the particular reaction of ATP with zeolitic imidazole framework-90 (ZIF-90) encapsulated laccase microcrystals (laccase@ZIF-90) and the natural catalytic activity of laccase.